Prescription Pattern of Primary Osteoarthritis in Tertiary Medical Centre - Kanneppady, Sowmya Sham; Kanneppady, Sham Kishor; Raghavan, Vijaya; Oo, Aung Myo; Lwin, Ohn Mar (Journal of Health and Allied Sciences NU, 2017)
Objectives: Osteoarthritis (OA) is one of the commonest joint/musculoskeletal disorders, affecting the middle aged and elderly, although younger people may be affected as a result of injury or overuse. The study aimed to analyze the data, evaluate the prescription pattern and rationality of the use of drugs in the treatment of primary OA with due emphasis on the available treatment regimens.Materials and methods: Medical case records of patients suffering from primary OA attending the department of Orthopedics of a tertiary medical centre were the source of data. The study was carried out prospectively for a period of 20 months (from December 2012 to July 2014).Results: 296 case records were collected in which the total number of drugs prescribed were 550. OA was more common in females (51.7%) and was more prevalent in the age group of 30–40 years (39%). Out of 550 drugs prescribed, Aceclofenac was the most frequently prescribed NSAID (29%) followed by Diclofenac (23%). Nimesulide and Paracetamol was the most commonly prescribed fixed dose combination (53). Among gastroprotectives, Ranitidine figured in 66 prescriptions. Glucocorticoids were prescribed orally and intraarticularly in 17 and 14 cases respectively. Dietary supplements like Calcium+Vitamin D (42) and Glucosamine Sulfate + Chondroitin Sulfate complex (19) were also prescribed.Conclusion: The above study highlights the rational use of therapeutic agents for primary OA.
Keywords: Osteoarthritis; anti-inflammatory agents; prevalence